Determinants of Investment Intention on Islamic Financial Technology for Milennial: Extended Theory of Planned Behavior - Misroh, Dina; Hermala, Irvan (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
This research aims to analyze the determinants Millennials’ behavior intention to invest on Islamic fintech platforms using the Theory of Planned Behaviour approach, which considers the variables of attitude, subjective norms, and perceived behavioural control, along with the addition of religiosity as an extension of the theory. Design of this research is a quantitative study using a descriptive causal method. The population of this study is Millennials who are born between 1980s and 1990s. The sample in this study consisted of 100 respondents selected using purposive sampling techniques. Data processing using SPSS 2023 software for descriptive analysis and SmartPLS 2023 software to analyse research data using the Partial Least Square method (PLS). The results of this study indicate that attitudes, subjective norms, perceived behavioural control, and religiosity have a positive and significant influence on Millennial’s behavioral intention to invest on Islamic fintech platforms. The determinant that has the greatest and most dominant influence on their intention at Islamic fintech is subjective norms. The results of this research can serve as recommendations for the Islamic fintech industry in its efforts to expand its market share among Millennials. This research utilizes an extension of the theory of planned behaviour by adding the aspect of religiosity as a determinant of Millennials’ intention in adopting Islamic fintech platforms, which has not been previously studied by prior researchers.